Association of TNF rs668920841 and INRA111 polymorphisms with caprine brucellosis: A case-control study of candidate genes involved in innate immunity - Hasenauer, Flavia Carolina (2020)
Caprine brucellosis is an infectious, contagious zoonotic disease caused by Brucella melitensis. Multiple factors, including host genetics, can influence the outcome of the exposure to Brucella; and it is expected that genetic variants that affect the host innate immune response could have a key role in Brucella infection and pathogenesis. In this study, we evaluated if polymorphisms in innate immunity-related genes are associated with results of Brucella infection in goats. Nine polymorphisms within interferon gamma (IFNG), tumor necrosis factor (TNF), MyD88 innate immune signal transduction adaptor (MYD88), interleukin 10 (IL10) and IL-10 receptor subunit alpha (IL10RA) genes and two molecular markers (BMS2753 and INRA111) were resolved by PCR-capillary electrophoresis in samples from 81 seronegative and 61 seropositive goats for brucellosis. A heterozygous genotype at INRA111, a microsatellite near the VRK serine/threonine kinase 2 (VRK2) gene, was associated with absence of Brucella-specific antibodies in goats naturally exposed to the pathogen (P = .004). Conversely, variants in the TNF gene (rs668920841) and near the IFN gamma receptor 1 (IFNGR1) gene (microsatellite BMS2753) were significantly associated with presence of Brucella-specific antibodies at allelic (P = .042 and P = .046) and genotypic level (P = .012 and P = .041, respectively). Moreover, an in silico analysis predicted a functional role of the insertion-deletion polymorphism rs668920841 on the transcriptional regulation of the caprine TNF gene. Altogether, these results contribute to the identification of genetic factors that have a putative effect on the resistance / susceptibility phenotype of goats to Brucella infection.